Stakeholders’ Perceptions of the Communication of the Territorial Brand: The Case of Braganca - Correia, Ricardo; Marinho, Madalena; Sousa, Bruno; Venciute, Dominyka (Journal of Tourism Management Research, 2022)
Territorial marketing aims to build a long-term strategy to structure and communicate territorial offers and integrates several elements that are essential for successful implementation. The local community, from residents to firms, is a fundamental element in the success of this strategy. This paper analyzes the perceptions of different stakeholders regarding their involvement in the strategic process of marketing the municipality of Bragança (a historical municipality in the northeast of Portugal) as a tourist destination. This study employed a mixed methods methodology. In the first part (qualitative analysis), interviews were carried out with the different competent bodies in the promotion and communication of the destination and with the county’s tourist entities. In the second phase (quantitative analysis), questionnaire surveys were conducted in the local community to complement the first part of the methodology. The results show little involvement of tourism entities in the construction and communication of the destination, as well as some gaps in identification with the destination. These results reinforce and justify the importance of the local community in marketing territories (which is fundamental), as well as the construction of a set of recommendations aimed at solving some of the problems found through the adopted methodology.